DEVELOPMENT OF A DIGITAL-BASED TEACHING MATERIAL MODEL FOR CIREBON LEGEND TEXTS - Aulia Fauziah; Miftahulkhairah Anwar; Novi Anoegrajekti (Erudio Journal of Educational Innovation, 2023)
The scarcity of supplementary teaching materials that teachers and students can use in learning the literary of Cirebon Legend in the digital era gives rise to the urgency to develop digital-based supplementary teaching materials of fantasy texts following the Merdeka (Independence) Curriculum. This research aimed to create digital-based teaching materials of Cirebon Legend texts as an application that serves as supplementary teaching materials for seventh-grade students in Junior High Schools (SMP). This research used the Research and Development (R&D) model, according to Borg and Gall. The components of teaching materials include four aspects: content aspect, presentation aspect, language and readability aspect, and graphic (visual) aspect. These aspects were used in the validity test by expert lecturers and teachers and in students’ response questionnaires. This research found that the digital-based teaching materials of Cirebon Legend texts for seventh-grade students received positive responses and are eligible for further use as supplementary teaching materials.